2017
DOI: 10.1088/1742-6596/852/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

Year to year variation of rainfall rate and rainfall regime in Ota, southwest Nigeria for the year 2012 to 2015

Abstract: Abstract. The tropics is characterized to have convective type of rainfall which has high occurrence of rainfall compared to the temperate regions of the world. In this paper, the accumulation of rainfall in Ota, Southwest, Nigeria (6 o 42 N, 3 o 14 E) has been analysed to present the one-minute rainfall rate and the predominant type of rainfall. Four years' data used for this study was taken using the Davis Wireless vantage Pro2 weather station at Covenant University, Ota, Ogun State. The data collected were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…During this decade-long observation, the maximum recorded rainfall rate was 33 mm/h in 2006, while the minimum rate of 4 mm/h occurred during the drier years of 2011 and 2012. The average measured rainfall rate over this ten-year period was determined to be 16.5 mm/h, enhancing the accuracy of rainfall rate performance characterization for the region [47], [48].…”
Section: Rainfall Characteristics In Uaementioning
confidence: 94%
See 1 more Smart Citation
“…During this decade-long observation, the maximum recorded rainfall rate was 33 mm/h in 2006, while the minimum rate of 4 mm/h occurred during the drier years of 2011 and 2012. The average measured rainfall rate over this ten-year period was determined to be 16.5 mm/h, enhancing the accuracy of rainfall rate performance characterization for the region [47], [48].…”
Section: Rainfall Characteristics In Uaementioning
confidence: 94%
“…To capture regional nuances, rainfall rates have been closely monitored in the northeastern region, including the installation of a tipping bucket rain gauge at Sharjah International Airport. Accurate annual rainfall data is essential [20], [47], [48]. Over a ten-year period (2005 to 2014), average rainfall rates were meticulously measured and recorded, as illustrated in Fig.…”
Section: Rainfall Characteristics In Uaementioning
confidence: 99%
“…The rainfall data was analysed by sorting and classifying the rainfall rate into four different categories, namely: the drizzle rain type (below 5 mm/h); the widespread rain type (between 5 mm/h and 10 mm/h); the shower rain type (between 10 and 40 mm/h) and the thunderstorm rain type (above 40 mm/h). Although, both rainfall and non-rainfall measurements are ongoing by some researchers in Nigeria [3], [4], [5], [6], [7], [8], [9], [10], [11], [12], [13]. Some descriptive statistics data measurement was also used by [14], [15].…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…The estimation of precipitation rate from radar gives a better spatial coverage than the rain gauge in a gauging station [2,9]. The rate at which precipitation is detected and recorded by the radar depends on the terminal speed of the rain drop [10][11][12]. This is classified in Table 1 according to World Meteorological Organization [13].…”
Section: Introductionrmentioning
confidence: 99%
“…The work of [5,7,15] showed that the spatial precipitation variations, its annual cycles, and diurnal are determined largely by how frequently it rains rather the intensity of the rain. Also, the rate of dominance of precipitation is ranges light to moderate rain [16], and its highest precipitation rate is at the intertropical convergence zone [5,11]. [17] showed that the seasonal cycle frequency and its spatial distribution can be likened to the rate of precipitation although, the rate of rainfall range inversely with the frequency peak.…”
Section: Introductionrmentioning
confidence: 99%